KONTRIBUSI MOTIVASI BELAJAR DAN SARANA PRASARANA TERHADAP HASIL BELAJAR MATA DIKLAT MENERAPKAN DASAR-DASAR TEKNIK DIGITAL KELAS X JURUSAN TEKNIK AUDIO VIDEO SMK N 1 PADANG - Dana Prastyo; Sukaya Sukaya; Almasri Almasri (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The problem in this study is the fact that the field is found in SMK Negeri 1 Padang, a class X student learning outcomes Technik Audio Video obtaining substandard minimum completeness criteria in subjects assigned Menerapkan Dasar - Dasar Teknik Digital school is 70.00. The purpose of this study was to reveal the contribution of the motivation on learning and facilities and infrastructure outcomes of students in subjects the Menerapkan Dasar - Dasar Teknik Digital in majors class X Technik Audio Video at SMK Negeri 1 Padang. This is a descriptive correlational study. The population in this study was student of class X at SMK Negeri 1 Padang are 62 students. While this research sampling technique is proportional random sampling. The sample in the study were 38 students of class X in SMK Negeri 1 Padang. Data were analyzed using SPSS (Statistical Product and Service Solutions). From the results, (1) motivation on learning (X1) to contribute to student learning outcomes of 18.8% (2) facilities and infrastructure (X2) to contribute to student learning outcomes of 38.8% and (3) The percentage contribution of variable motivation on learning (X1) facilities and infrastructure (X2) jointly to the student learning outcomes (Y) is equal to 48.1%. This shows the better motivation on learning and facilities and infrastructure to learn the students' learning outcomes will be better anyway. Keyword: Motivation on Learning and Facilities and Infrastructure. Menerapkan          Dasar-Dasar Teknik Digital.